Globalisation, Structural Change and Labour Productivity Growth in BRICS Economy - Jagannath Mallick (FIW - Research Centre International Economics, 2015)
Globalisation, has intensified the demand preference for quality labour, that embodies more knowledge and competency/skill to maximise the production in one hand, and it has also changed the life style and consumption behavior of the society on the other. As a consequence, this has led to significant changes in the composition and structure of the economy, and also, the reallocation of labour. The study examines the reallocation effect (or structural change) and the direct effect of globalization on labour productivity growth in BRICS countries. The study also examines the relative role of consumption factors and other factors for the structural development during globalization. The study uses shift-share analysis, dynamic panel data method and input-output tables for the empirical analysis during 1990-91 to 2011-12. The findings show that the contribution of structural change is relatively significant in China and India. The globalization measures including international trade and FDI are found to have significant impact on the upsurge of labour productivity growth in BRICS, where the consumption demand predominates among the factors of structural development.
Keywords: F1; J01; J08; J34; R1; 330; Globalisation; FDI; Trade; Labour productivity; Structural Change; BRICS